Non-Relativistic Finite Difference Time Domain Method for Electromagnetic Problems with Moving Bodies - Marvasti, Mohammad; Boutayeb, Halim (International Conference on Numerical Electromagnetic Modeling and Optimization for RF, Microwave, and Terahertz Applications (Online), 2023)
By using the Finite Difference Time Domain (FDTD) method, this paper presents an original analysis of electromagnetic problems with moving bodies. In our FDTD program, movements are implemented by changing positions of the objects at different time instants, through the classical FDTD time loop. With this direct approach, time is implicitly absolute and Voigt-Lorentz transformations are not implemented. This technique is suitable for non-relativistic speeds, thus for most encountered electromagnetic problems. We present the numerical aspects that need to be considered in the FDTD code. Then, different problems are investigated with new results: moving plane wave source with matching resistors, moving dielectric half-space and moving metallic cylinder.